Use of Randomly Amplified Polymorphic DNA (RAPD) Markers in Poultry Research - Salem, H.; Ali, B.; Huang, T.; Qin, DN. (International Journal of Poultry Science, 2005)
Random amplified polymorphic DNA (RAPD) markers can be generated using short arbitrary primers to amplify genomic DNA, giving a genotype-specific pattern of bands. RAPD analysis should lead to the saturation of the genome without the requirement of previous genetic information and using few expensive oligonucleiotides. The use of DNA marker technology in poultry as a strains identification has progressed rapidly during the last decade. This review summarizes the use of RAPDs as molecular markers in poultry research, especially in some genetic resources of economically important species such as chickens, quails, ducks, goose, turkey and other birds. Also we discuss its limitations and benefits including its simplicity and ease of use in the laboratory.